Inducing Ring Complexation for Efficient Capture and Detection of Small Gaseous Molecules Using SERS for Environmental Surveillance. (4th July 2022) - Nguyen, Lam Bang Thanh; Leong, Yong Xiang; Koh, Charlynn Sher Lin; Leong, Shi Xuan; Boong, Siew Kheng; Sim, Howard Yi Fan; Phan‐Quang, Gia Chuong; Phang, In Yee; Ling, Xing Yi
Abstract: Gas‐phase surface‐enhanced Raman scattering (SERS) remains challenging due to poor analyte affinity to SERS substrates. The reported use of capturing probes suffers from concurrent inconsistent signals and long response time due to the formation of multiple potential probe–analyte interaction orientations. Here, we demonstrate the use of multiple non‐covalent interactions for ring complexation to boost the affinity of small gas molecules, SO2 and NO2, to our SERS platform, achieving rapid capture and multiplex detection down to 100 ppm. Experimental and in‐silico studies affirm stable ring complex formation, and kinetic investigations reveal a 4‐fold faster response time compared to probes without stable ring complexation capability. By synergizing spectral concatenation and support vector machine regression, we achieve 91.7 % accuracy for multiplex quantification of SO2 and NO2 in excess CO2, mimicking real‐life exhausts. Our platform shows immense potential for on‐site exhaust and air quality surveillance. Abstract : Practical applications of gas‐phase surface‐enhanced Raman scattering (SERS) suffer from poor analyte affinity to plasmonic substrates, low concentration, and inherently small Raman cross‐sections. Herein, ring complexation is leveraged via formation of multiple non‐covalent interactions with small gases to yield effective capture and distinct spectral changes for multiplex detection of SO2 and NO2 in excess of CO2 mimicking artificial exhaust.